(3eQBI GdReGf aj JGQjN GdCYjGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s
(3ChdgG (B:s
(3jHOC HaUd ai bUi MRbjd Ydjg GdSdGe s
(3BNQgG (B:s
(3jfJgi HaUd ai CjGe GdYQH s
(3fSNI fajSI bOjeIs
(3JedcgG jhSa cJNOG eMeO MGce HfOQ SfI (B1088(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1647s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs